Origin of brown coloration in top-seeded solution grown SrTiO3 crystals. Issue 24 (17th May 2016) - Kok, Dirk J.; Guguschev, Christo; Markurt, Toni; Niu, Mutong; Bertram, Rainer; Albrecht, Martin; Irmscher, Klaus
Abstract : The brown coloration in top seeded solution grown SrTiO3 crystals is investigated and found to be caused by nanometer sized voids. Abstract : SrTiO3 crystals grown by the top-seeded solution growth method in air show different shades of light brown coloration, depending on the growth conditions. In the optical transmission spectrum this is manifested as a broad absorption, tailing off from the fundamental absorption edge into the visible range. The investigation by transmission electron microscopy reveals that the light brown crystals contain voids of varying sizes in the nanometer range. Using the found size density distribution, the light scattering caused by such nano-voids in SrTiO3 is calculated on the basis of the Mie theory. A good agreement with the measured optical spectra is found. It is proposed that the formation of the nano-voids is due to vacancy clustering.